BROOD-STOCK REARING AND ARTIFICIAL BREEDING OF SCHIZOTHORAX RICHARDSONII (GRAY) - Joshi, Kripal Dutta (Journal of the Inland Fisheries Society of India, 2016)
BROOD-STOCK REARING AND ARTIFICIAL BREEDING OF SCHIZOTHORAX RICHARDSONII (GRAY)